Ecological variability based on lipid biomarkers in astrobiologically interesting wetlands from the Argentinian central Andes. Issue 5 (28th April 2022) - Carrizo, Daniel; Vignale, Federico A; Sánchez-García, Laura; Farías, María E
Abstract: Andean wetlands hold extremophilic communities adapted to live in harsh conditions. Here, we investigated the microbial ecology of three high-altitude hypersaline ponds from La Puna region (Argentina) showing an increasing extent of desiccation by analyzing their lipid sedimentary record. We recreated the microbial community structure and the carbon metabolisms in each lacustrine system based on the molecular distribution of lipid biomarkers and their compound-specific carbon and hydrogen isotopic signatures. We detected lipid compounds considered to be biomarkers of cyanobacteria, sulfate-reducing bacteria, purple sulfur bacteria, and archaea in the three Andean ponds, as well as diatoms in the intermediate salinity system. The relative abundance of purple sulfur and sulfate-reducing bacteria decreased with salinity, whereas cyanobacteria and archaea decreased their relative abundance in the mid-saline pond to increase it again and became both prevailing at the highest salinity. Carbon fixation in the three ponds was driven by a combination of the reductive tricarboxylic acid cycle, the reductive pentose phosphate cycle, and the reductive acetyl-CoA pathway. This work is the first to describe molecular and isotopic lipid fingerprints in wetlands from the central Andean Puna, and serves as a basis for further biogeochemical studies in the area. Abstract : First report on lipids biomarkers and their compound specific isotopic composition (carbon and hydrogen) in high-altitude hypersaline ponds.